An uncertain future. (Economist, 2012)
The article presents information on the 2012 annual meeting of the American Association for the Advancement of Science (AAAS) in Vancouver, British Columbia. Scientists including Charles Marcus, Michael Freedman, and John Martinis presented information on their research on subjects including quantum computing, quantum entanglement, superconductors, and quantum dots.